Muslim diaspora in the West negotiating gender, home and belonging - Moghissi, Haideh; Ghorashi, Halleh (Research in migration and ethnic relations series, 2010)
In view of the growing influence of religion in public life on the national and international scenes, "Muslim Diaspora in the West" constitutes a timely contribution to scholarly debates and a response to concerns raised in the West about Islam and Muslims within diaspora. Presenting the latest research from a variety of locations on both sides of The Atlantic, "Muslim Diaspora in the West" addresses the realities of diasporic life for self-identified Muslims, addressing questions of integration, rights and equality before the law, and challenging stereotypical views of Muslims. As such, it will appeal to scholars with interests in race and ethnicity, cultural, media and gender studies, and migration.